ESL students english business skills development (based on the authentic movies «The Devil Wears Prada» and «Promised Land») - Irina Y. Sukhanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article focuses on the possibility and necessity for the ESL teachers to develop ESL students business communicative skills during their classes. The author introduces requirements necessary for improving effective ESL students activity, shares some experience of using original movies and textbooks as a means of ESL students work and presents various types of tasks for studentsAccording to the state educational standards of higher education a modern specialist should do self-study, using modern educational and information technologies, understand the diversity of social, cultural, ethnic, religious valuesand differences, knowways and means of cultural communication.The main goal of our study is to create the complex of exercises in order not only to keep up students motivation to the following subject but also to develop their communicative skills and business communicative skills. Achieving this we can accomplish a number of pedagogical tasks. The conclusions are proved by numerous examples. The complex of exercises done before, while and after watching is presented. The authors analyze the combination of video sequence and audio sequence and their sociocultural contents.We would like to emphasize that using original movies is very important for this purpose. It is also necessary to create course-books based on business vocabulary andcross-cultural material. The article makes a conclusion that proper authentic moviesintroduce peculiarities of business English and etiquette to the students, keep up their motivation and improve their communication skills.